Velocity determination of Kathmandu Complex - Pandey, M. R. (Journal of Nepal Geological Society, 1981)
Longitudinal and transverse wave velocity of the Kathmandu Complex has been determined based on the arrival times of seismic waves from Kulekhani Dam Quarry blasts, at Phulchaki, Daman and Kakani stations of the Kathmandu Tripartite seismic network by least square method.